Assessment of Serum Visfatin Levels in Patients with Chronic Obstructive Pulmonary Diseases in Babylon-Iraq - Hamood Hathala Salman1 , Ban Mahmood Shaker Al-joda2 , Monem Makki Abdulridh Alshok3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The presented study aims to evaluate of the levels of serum Visfatin, in patients with chronic obstructive Pulmonary diseases in Babylon-Iraq , to find the correlation of Visfatin, with lipid profile in these patients and compared with apparently healthy as case – control study. The study included (50) patients as patients group diagnosed with COPD (G1) and (50)as apparently control group(G2) .The age of all studied groups ranged between (40-65)years and BMI with (18.8-24.4) Kg/m2 .Serum was used in determination of FBS, lipid profile( Ch,TG,HDL-c,LDL-c and VLDL-c) , insulin , CRP and Visfatin , Whole blood was used for determination of HbA1C . The results revealed significant elevation in FBG and HbA1c levels were seen in patients groups when comparing to healthy control .The results indicates a significant elevation in TC, TG ,LDL-c and VLDL-c in G1 comparing to G2. Also , HDL-c significant decreased in G1 comparing to G 2 , Also ,the results showed significant increased in CRP levels in G1 , when comparing to G2, A non significant visfatin and insulin level in G1 when compared with G2(p value = 0.486) , . A non significant correlation was found in G1 between visfatin ,TC,TG, HDL-c and VLDL-c. The conclusion from this study indicate that G1 which HDL-c is low in this group has the highest value for FBS , HbA1c , TC ,TG,LDL and VLDL .Also, the study found non correlation between lipid profile parameters in G1